Copper-based reversible electrochemical mirror device with switchability between transparent, blue, and mirror states - Eh, Alice Lee-Sie (2017)
Reversible electrochemical mirror (REM) device can be electrochemically tuned to exhibit dual transmittance and reflectance modulations in a single device. Conventional REM devices reversibly switched between transparent and mirror states. However, it is of great challenge to maintain the mirror state of the REM devices due to the diffusion of anions into the metallic film at the open-circuit state. In this work, we report a Cu-based REM device which offers reversible switching between transparent, blue and mirror states with judicious selection of electrolyte and controllable electrodeposition. The blue state can be obtained through the formation of copper (I) chloride, CuCl, when copper (II) chloride CuCl2 undergoes electrochemical reduction. The polymer host, PVA (poly(vinyl alcohol)) plays an important role in reducing the surface roughness of the electrodeposited mirror film, improving film uniformity and sustaining the mirror state of the device during the voltage-off state.